PERAN KELURAHAN DALAM VERIFIKASI DAN VALIDASI DATA KEMISKINAN EKSTREM DI KELURAHAN MARGASARI KOTA TANGERANG - Foharato Gulo; Udin, Wawan (LP3kM Buddhi Dharma University, 2025)
Accurate data on extremely poor households determines the effectiveness of extreme poverty alleviation programs, so the process of verifying and validating (verval) extreme poverty data needs to be carried out. This study aims to determine the role of the sub-district in verifying and validating extreme poverty data in Margasari Sub-district, Karawaci District, Tangerang City, and to identify the obstacles encountered in the verification and validation process. The background of this research focuses on the importance of accurate poverty data for more targeted policy planning, but there are still challenges in the process of verifying and validating data in the field. The method used in this study is a qualitative approach, conducting interviews and observations in Margasari Sub-district to explore information related to the implementation of verification and validation as well as the obstacles that arise. The results of this study show that the role of the sub-district in the implementation of extreme poverty data verification and validation includes coordination with RT/RW, community leaders, and related parties, conducting field verification, validation through sub-district deliberations, and reporting the results of verification and validation to higher authorities. This shows that the sub-district does not only act as an administrative implementer, but also as a facilitator and liaison between government policies and the community. The obstacles encountered in the implementation of verification and validation include limited human resources, inaccuracy of initial data from the central government, resistance from some members of the community to the data collection process, and limited information technology facilities.